(untitled) (LEARNing Landscapes, 2013)
The focus of this article is on lessons learned about teaching through the online environment from the experience of 120+ instructors who transitioned from teaching in a traditional face-to-face environment to a blended synchronous and asynchronous online world. We admit that we entered the synchronous virtual world with faulty assumptions and misplaced confidence, believing that what worked in the brick-andmortar world should also work, with little adaptation, in the virtual world. There continues to be so little literature about teaching in the synchronous virtual environment that we had to rely on our ability to learn quickly by trial and error.